Review of two sustainability learning programmes for industrial settings in relation to emerging green learning aspects - Visagie, Martha Jacoba (Rhodes University, Faculty of Education, Department of Education, 2015)
Driven by the needs of growing populations, industrial and governing powers are successfully accelerating the rate of industrial consumption, production and employment as if the earth's resources are in unlimited supply. In contrast, a range of international sustainable development forums, inspired by visionary individuals, have made significant progress in creating awareness that the footprint of human activity is exceeding the earth's sink and source capacity; and educating people in government, workplaces and communities to slow down industrial consumption and clean up production. Turning around conventional and short sighted 'business as usual' logic, and directing economies toward greener, long-term sustainability outcomes, still meet with resistance and hidden unsustainable agendas. The 'green economy' drive nevertheless since 2008 attracts financial and human resources and bold action in favour of more sustainable management of human-nature relations. The sustainable development movement for example advocates a 'triple bottom line' approach, holding that socially and ecologically responsible economic development would be sustainable. The sustainability movement has attained significant buy-in among governments and business communities. It forms the under-labouring philosophy of the programmes reviewed in this case study. The thesis reviews social-economic events paving the way for a global green economy. Taking a leadership role in the sustainable development movement the United Nations (UN) and the Organisation for Economic Co-Operation and Development (OECD) concurred to respond to the 2008 world-wide economic meltdown with a two-pronged 'Green New Deal' (UNEP, 2008). The Green New Deal financial package helps restore multi-national economic growth, employment and markets while re-shaping economies to follow an ecologically and socially responsible growth trajectory. South Africa implements green economy principles as part of the 2010 The New Growth Path overarching policy framework, with an implementation strategy embedded in the 2011 National Development Plan (NDP) (RSA. The Presidency, 2010; 2011). The New Growth Path emphasises that the transformation of South Africa's un-sustainable economic and educational legacy to a more sustainable future is not expected to follow a smooth, linear process. The transition to a green economy is rather expected to be an event of ""¦ noisy, healthy democracy" (RSA. The Presidency, 2010). A green, low carbon economy particularly constitutes a pledge to slow down and turn the human induced climate change trajectory around. McKinsey (2009) argues that this pledge is attainable on a world-wide scale, as sufficient and suitable environmentally sound techniques and technologies are already in place. Attaining buy-in from business stakeholders toward re-thinking and amending an economy's self-defying large environmental footprint (inclusive of carbon, water and waste footprints) however requires education starting with awarenessraising followed by educational programmes and official curricula aimed at implementation and continuous improvement of green practices in day to day 'doings and beings' (Sen, 1997). This study at implementation level reviews two green economy training programmes and their emergence in South Africa around this rationale. The awareness generation and training programmes elected as case study examples are the 'Resource Efficient and Cleaner Production' (RECP) and 'Industrial Energy Efficiency' (IEE) programmes, of the hosting agency National Cleaner Production Centre of South Africa (NCPC-SA). The RECP and IEE teams reach out to decision makers, engineers and artisans at industrial workplaces and workplace related events to add green competences to their business-as-usual skill sets. Implementing green options in industry typically slows down industrial scale resource consumption, pollution, waste generation and green-house gas (GHG) emissions while optimising resource productivity and enterprise excellence. Optimised supply side systems allow industry to reduce energy and material intensity of products thus reducing cost and producing more with less. In transitioning to a 'Green GDP' economy South Africa is awakening to the reality that natural resources constitute the original, albeit limited feedstock for growth and employment. The RECP and IEE approach also contribute to reduction of industrial waste, waste-to-landfill, and energy and resource security. Literature reviewed for this research provides evidence that the green economy's triple bottom line philosophy is quantifiable thus manageable. A range of green economy management tools are emerging, including guidelines for carbon, water and environmental footprinting and the green-house gas abatement cost curve (see section 2.2.5) (McKinsey and Company, 2009). Transitioning from business as usual to ecologically sustainable industrial sectors however requires visionary, educated leadership, willing and capable of introducing modern and more efficient techniques and technologies. The boundaries of this half thesis embrace the globally and historically significant Tbilisi Declaration and other education and sustainable development agreements produced by United Nations and OECD mechanisms. Participating nations like South Africa incorporate the essence of these agreements into domestic policies and strategies, and align industries to remain competitive in international markets, which are increasingly enforcing green standards like ISO 14001 and ISO 50001. The focus of this case study guided by inductive, abductive and retroductive inference is to understand how the two sustainability learning programmes for people in industrial workplaces, supported by the United Nations Industrial Development Organisation (UNIDO) and relevant donors, and overseen by the South African Department of Trade and Industry (the dti), relate to emerging green learning aspects. Producing a review of this nature requires a framework of laterally understanding emerging green learning aspects, for which I have reviewed green economy literature and also green learning and conventional education and training literature respectively. Themes emerging from the literature review informed an analytical instrument (questionnaire) in Phase One. In Phase Two the questionnaire was applied through nested case study methodology to show how the educational content and approaches of the RECP and IEE programmes relate to emerging green learning aspects and as such is suitable for mainstreaming in the national educational system. From an explicit educational perspective potential partners for collaboration include the Department of Higher Education and Training (DHET) the South African Qualifications Authority's (SAQA's) Quality Council for Trades and Occupations (QCTO) and the Sector Education and Training Authorities (SETAs) representing the training needs of the industrial workforce but affiliated to QCTO and SAQA. In the extended scenario the NCPC-SA as a dti programme recognises the Department of Environmental Affairs (DEA) as lead agency guiding implementation of South Africa's green economy, and specifically DEA's National Environmental Sector Skills Planning Forum (NESPF), a national leader in green skills development in South Africa, as conduit for productively mainstreaming relevant RECP and IEE content and approaches toward green skills development for the green economy.
Keywords: Environmental education; Sustainable development -- Study and teaching (Continuing education); Natural resources -- Management -- Study and teaching (Continuing education); Environmental economics -- Study and teaching (Continuing education); Green movement